2017
DOI: 10.1007/s00216-017-0754-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of therapeutic protein AvidinOX by an integrated analytical approach

Abstract: AvidinOX, the oxidized derivative of Avidin, is a chemically modified glycoprotein, being currently under clinical investigation for targeted delivery of radioactive biotin to inoperable tumors. AvidinOX is produced by 4-hydroxyazobenzene-2-carboxylic acid (HABA)-assisted sodium periodate oxidation of Avidin. The peculiar property of the periodate-generated glycol-split carbohydrate moieties to form Schiff's bases with amino groups of the tissue proteins allows to achieve a tissue half-life of 2 weeks compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…62 Attempts to uniquely improve trastuzumab efficacy are also coming from our group at Alfasigma SpA. From our long experience in tumor pre-targeting based on the exploitation of the avidin-biotin interaction, [63][64][65][66][67][68][69] we recently found that by anchoring biotinylated trastuzumab or pertuzumab to AvidinOX (modified avidin chemically reacting with tissue proteins)-treated tumor cells, antibody reactivity is increased by several orders of magnitude. 70 This peculiar phenomenon, which is related to the inhibition of the targeted receptor trafficking, could allow significant reduction of antibody doses with consequent reduction of toxicity and costs.…”
Section: New Products/new Mechanisms Of Actionmentioning
confidence: 99%
“…62 Attempts to uniquely improve trastuzumab efficacy are also coming from our group at Alfasigma SpA. From our long experience in tumor pre-targeting based on the exploitation of the avidin-biotin interaction, [63][64][65][66][67][68][69] we recently found that by anchoring biotinylated trastuzumab or pertuzumab to AvidinOX (modified avidin chemically reacting with tissue proteins)-treated tumor cells, antibody reactivity is increased by several orders of magnitude. 70 This peculiar phenomenon, which is related to the inhibition of the targeted receptor trafficking, could allow significant reduction of antibody doses with consequent reduction of toxicity and costs.…”
Section: New Products/new Mechanisms Of Actionmentioning
confidence: 99%